KAJIAN KESESUAIAN KUALITAS AIR UNTUK PENGEMBANGAN KERAMBA JARING APUNG DI PULAU SERANGAN, BALI - Ernawati, N.M.; Dewi, A.P.W.K. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
The marine water area of Serangan Island has been used for several activities such as aquaculture, captured fisheries, ships transportation, tourism and also area for leachate discharge from Suwung waste area. Those activities resulted in the decrease of water quality which has negative effect on the cage net culture activities, especially that low water quality decrease the immune system of the cultured organisms. So far, the feasibility of water quality for cage net culture activity in Serangan Island has not been identified. The objective of this study is to investigate the water quality and its feasibility for the development of cage net culture activity in that area. This study use descriptive and explorative methods to figure out the actual condition of water quality and its feasibility for cage net culture development in marine water area of Serangan Island. Some measured parameters are water depth, current velocity, temperature, salinity, pH, DO, BOD, Ammonia (NH3-N), oil and lipid content, and lead (Pb). The results show that in Serangan Island marine water area, the water quality range as follow: temperature 26-28 °C; Salinity 23-26,67 ppt; pH 7,4-7,9; dissolved oxygen (DO) 1,5-6 mg.l-1; BOD 6,1-8,2 g.l-1; NH3-N 0,4-0,9 mg.l-1; oil and lipid content <0,1; lead (Pb) cannot detected (<0,0036 mg.l-1); current velocity 0,2-0,6 cm.s-1; and the water depth 5,5 – 9,4 m. Generally, those measured water quality parameters are feasible for marine culture using cage net culture system.
Keywords: Cage net culture, Serangan Island marine water, Water quality